Digitalizing Teaching At The Right Level (TARL): An Online Assessment System for Mapping Literacy Competencies in Primary Education - Marzoan; Purmadi, Ary; Yasin, Mohd Hanafi Bin Mohd (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop and validate ASI ASLI (Aplikasi Sistem Asesmen Literasi), an online-based literacy assessment and decision-support system designed to map elementary school students’ reading competencies and support differentiated instruction aligned with the Teaching at the Right Level (TaRL) framework. This study employed a research and development (R&D) approach adapted from Borg and Gall, with the development process conducted up to the main field testing stage through large-scale implementation in primary schools in Central Lombok Regency. A total of 4,058 students in Grades III–V participated, selected using a multi-stage cluster sampling strategy across urban, coastal, and rural contexts. Data were collected through literacy assessments embedded in the ASI ASLI system, expert validation instruments, teacher response questionnaires, and classroom observations, then analyzed using a mixed-methods approach. Findings indicate that ASI ASLI demonstrates strong technical feasibility, usability, and instructional relevance. Competency mapping revealed gradual improvement across grade levels; however, a substantial proportion of students remained at the Special Intervention and Basic levels, with pronounced disparities in rural areas. These findings highlight the urgent need for differentiated, data-informed instructional interventions and targeted policy support to address foundational literacy gaps.